Impact of integrated management approaches on insect pests of mungbean - Panickar et al, Bindu (Indian Journal of Plant Protection, 2018)
n experiment was conducted at Pulses Research Station, Sardarkrushingar Dantiwada Agricultural University, from 2014 to 2016 to develop integrated management modules against insect pest complex of mungbean/green gram. Amongst the modules tested, MII module [seed treatment with Trichoderma harzianum @ 4 g/kg + imidacloprid 600 FS @ 5 ml/kg of seed, installation of yellow sticky traps @ 50/ha, spraying of neem seed kernel suspension 5% around 30 days after sowing (DAS) and triazophos @ 1.0 ml/l at 45-50 DAS] was most effective against sucking pests. Whereas, MI module (seed treatment with T. harzianum @ 4 g/kg + imidacloprid 600 FS @ 5 ml/kg of seed, installation of yellow sticky traps @ 50/ha, spraying of neem seed kernel suspension 5% around 30 DAS and novaluron @ 1 ml/l at 45-50 DAS) was also effective against pod borers in mungbean.